Witchcraft and sumpah pocong: Transformation and resolution of cases with the issue of shamans in Banyuwangi - Kusairi, Latif (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
Many people believe that misfortunes such as illness, death, crop failure, livestock death, and divorce are caused by certain people with magical powers and knowledge called